A társadalmi gazdaság posztszocialista sajátosságai Kelet-Közép-Európában - G. Fekete, Éva (Közép-Európai Közlemények, 2017)
Exploring post-socialist specifics of social economy in the East-Central-European countries are the objects of our ongoing research project titled “Social and solidarity economy in the postsocialist periphery” and supported by the Hungarian Scientific Research Fund Nr. K112928 contract. In addition to examining the very limited comprehensive and comparable data available internationally, an overwiew of the history and an analisys of determining factors of social economy help to identify differencies between social economies in Western and Eastern European countries. At the end we try to decide whether these differences indicate only a time delay or present a special east-central-european model in social economy. Verification of our twelve point hypothesis needs some additional investigations which are describe in the conclusion and will be completed by involvement of social economy experts from several East-Central-European countries.